Lost horizon - Hilton, James, 1900-1954. (New York : Pocket, 1960)
Conway, one of four people whose plane crashed while they were fleeing a civil war in a foreign land, is rescued along with the rest of his group by a mysterious Chinese man who takes them to safety in Shangri-la, a land of peace and beauty where they are offered near immortality on the condition that they never leave.
Library Journal.
Wilson's Fiction.
Wilson's Senior High School.
Young Adult
Keywords: Aircraft accidents -- Fiction; Fantasy; Aircraft accidents -- Fiction; Tibet (China) -- Fiction; Tibet (China) -- Fiction; Fantastic fiction